2020 Research Connections Unit Annual Report - Girard, Marie-Eve (Université d'Ottawa | University of Ottawa, 2021)
The uOttawa Research Connections unit is part of Research Management Services in the Office of the Vice-President, Research (OVPR). It was established to develop and implement the University of Ottawa Knowledge Mobilization Institutional Strategy 2019-2021. In 2020, the Research Connections Knowledge Mobilization Advisor, in collaboration with many uOttawa stakeholders and the members of the Research Connections Advisory Committee, implemented a range of activities designed to achieve the strategy objectives. The objectives aim to 1) build foundational knowledge and skills in knowledge mobilization, 2) promote the culture of knowledge mobilization, 3) engage knowledge users and 4) evaluate outcomes and generate impact. This report provides an overview of these accomplishments.
Keywords: Research Connections Unit; Knowledge Mobilization; Strategy